Critical Analysis of Rk Narayan’S Novel- a Tiger For Malgudi: Exploring the Fusion of Indian Mysticism and English Novel Form in R.K. Narayan's A Tiger For Malgudi (Journal of Advances and Scholarly Researches in Allied Education, 2013)
R. K. Narayan is considered one of the three best Indianauthors writing in English; the other two are Rao Raja and Mulk Raj Anand.Narayan's fiction contains a unique blend of Indian mysticism and the Englishnovel form. His fictional world, Malgudi, is one of everyday concerns andcommon language set in southern India, which he successfully portrays throughsubtle prose and humor.